Three cryo-EM structures of CD109 reveal its mechanism of protease inhibition - Ana V. Almeida; Kathrine T. Jensen; Seandean L. Harwood; Martin H. Jørgensen; Nadia S. Nielsen; Ida B. Thøgersen; Jan J. Enghild; Gregers R. Andersen (Cell Reports)
Summary: CD109 is a glycosylphosphatidylinositol-anchored protein. In addition to regulating transforming growth factor β (TGF-β) network signaling, CD109 is also a protease inhibitor. Protease cleavage of its bait region triggers a conformational change releasing the major fragment from the cell surface, exposing a reactive thioester that can conjugate proteases. To understand this protease inhibition mechanism, we determined cryoelectron microscopy structures of CD109 in native, protease-activated, and methylamine-activated conformations. Despite CD109’s low sequence similarity with the protease inhibitor A2ML1, CD109 adopts a similar protease-activated conformation, suggesting a shared mechanism of protease inhibition. Deglycosylation of CD109 does not affect chymotrypsin conjugation but enhances substrate access, suggesting that CD109 glycans contribute to protease inhibition. Our data provide a structural basis for understanding CD109’s protease-triggered membrane release, its protease inhibitory mechanism, and additional biological functions.